A DEMONSTRATION OF THE ROLE OF SCIENCE IN THE PROGRAMS OF EDUCATIONALLY DEPRIVED CHILDREN IN GRADES 7-9. - Bingham, N. Eldred (Science Education, 1968)
The article presents the role of science in the programs of educationally deprived children. It states that present science program plans to illustrate the use of the course as a tool in encouraging educationally disadvantaged youth to active participation in learning and to create science materials and approaches distinctively suited to challenge the educationally disadvantaged. The Duval County Public School System together with individuals who conducted the pilot demonstration of the science program for deprived children also developed a special program in science designed for 7th, 8th, and 9th grade levels called DISCUS and is carried out in fourteen schools, including schools having the highest percentage of educationally deprived underachieving youth.